Two-dimensional fretting contact analysis of piezoelectric materials. (November 2015) - Su, Jie; Ke, Liao-Liang; Wang, Yue-Sheng
Graphical abstract: The effect of the friction coefficient η on the tangential traction during cyclic tangential loading is presented. With the increase of the friction coefficient, the peak value of the tangential traction increases rapidly. Highlights: The coupling in contact increases the peak value of normal and tangential tractions. The peak value of tangential traction increases with the increase of friction coefficient. The piezoelectric effect leads to the concentration of normal and tangential tractions. Abstract: This paper makes the first attempt to present a theoretical study on the fretting contact of a piezoelectric half-plane under a rigid cylindrical punch. It is assumed that the rigid punch is a perfect insulating body with zero electric charge distribution. The two bodies are brought into contact first by a monotonically increasing normal load, and then by a cyclic tangential load which is less than that necessary to cause complete sliding. The whole contact region is composed of an inner stick region and two outer slip regions in which Coulomb's friction law is assumed. Since the fretting contact problem is frictional and history dependent, therefore we first solve the normal loading phase, and then solve the tangential loading phase. With the use of Fourier integral transform technique and the superposition theorem, the problem is reduced to a set of coupled Cauchy singular integral equations. An iterative method is used to determine the unknown stick/slip region and contact tractions. The effects of the friction coefficient and radius of the punch on the normal contact pressure, tangential traction, in-plane stress and in-plane electric displacement are discussed during different loading phases in detail. The results indicate that the piezoelectric effect leads to the concentration of the normal contact pressure and tangential traction, which may cause a serious influence on the fretting contact damage.